PENGARUH TEKNOLOGI POINT OF SALE (POS) BERBASIS CLOUD TERHADAP KECEPATAN DAN AKURASI SISTEM INFORMASI AKUNTANSI PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM): (Studi pada UMKM Sektor Makanan dan Minuman di Kota Surabaya) - April Lianingsih; Loggar Bhilwa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian Micro, Small, and Medium Enterprises (MSMEs) face inequality in the adoption of accounting technology, which causes reporting delays and a high risk of recording errors. This study aims to analyze the effect of the perceived ease of use and usefulness of cloud-based Point of Sale (POS) technology on the speed and accuracy of Accounting Information Systems (AIS), as well as the moderating role of digital competence. This research applies a quantitative approach using a survey method. Data were collected through a 1-4 Likert-scale questionnaire distributed to 100 food and beverage (F&B) MSME respondents in Surabaya City, selected through purposive sampling, and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS. The results indicate that both ease of use (sig. 0.000) and usefulness (sig. 0.000) of cloud-based POS have a positive and significant effect on the speed and accuracy of AIS. Digital competence was proven to strengthen both effects (sig. 0.009 and 0.040), with an Adjusted R Square of 50.1%. These findings confirm that the success of accounting digitalization among MSMEs is determined not only by the sophistication of the technology but also by the readiness of human resources to utilize it. MSME actors are advised to continuously improve their digital literacy so that the benefits of cloud POS can be optimized.